ANALISIS KELAYAKAN USAHA PETERNAKAN ITIK PETELUR DI HARUM SELALU FARM KEC. GEGER KAB. MADIUN PROPINSI JAWA TIMUR - Imang Deni Irmawan; Ahsin Daroini; Rohmad Rohmad (Universitas Islam Kadiri, 2018)
Duck farming in Madiun Regency is not without problems. The common problems faced by duck breeders are the increasingly expensive cost of feed. The feed cost has a composition of more than 70 percent of the total production cost or maintenance cost. The research was conducted at